BEZPIECZEŃSTWO IMPREZ MASOWYCH (uwagi na tle ustawy z dnia 22 sierpnia 1997 roku) - Tarnawski, Maciej; Tarnawski, Artur (Wydział Prawa i Administracji UAM, 1998)
The Authors discuss the law on security of mass events. This law determines: 1) necessary conditions for security of mass events, 2) procedure of granting licences for such events, 3) bases for responsibility of organizers of such events and of their attendants in case of a violence of the provisions of the law. The Authors discuss also dispositions of the law on police from 1990 which are complimentary to the law cited above. Some propositions de lege ferenda are also formulated, among others - especially concerning responsibility of the police and other subsidiary guards for irregular or illegal (conf. de lege lata) interventions during disturbed mass events, more particularly in sports.
SECURITY OF MASS EVENTS (REMARKS TO THE LAW FROM AUGUST 22, 1997)